New technologies and the demand for medium qualified labour in Germany - Jacobebbinghaus, Peter [Verfasser]; Zwick, Thomas [Verfasser] (My University, 2001)
"The literature on skill-based technological change concentrates on highly skilled and unskilled employees. the impact of innovation activities ou the majority of the labour force in Germany - emppoyees with a degree from the dual apprenticeship system - is unknown, however. The focus of this paper is the impact of new technologies on the situation of medium skilled employees. In addition, estimation and data problems are addressed in a topical and rich data set. The paper shows that innovation expenditures and investments in information and communication technologies lead to lower medium skilled employee shares, whereas other investments lead to lower medium skilled employee shares, whereas other investments lead to higher shares." (author's abstract, IAB-Doku) ((en))
Keywords: S 1.3.1 Ausbildung im Dualen System; S 4 Kosten & Finanzierung; G 2.2.1 Technologisierung; Duales System; Kosten; Technischer Wandel; Informationstechnik